Relationship between impulsivity and aggressiveness with mental disorders and suicide risk in cocaine/crack users - Santos, Ana Caroline Melo dos; Santos , Bruna Brandão dos; Farias , Karol Fireman de; Alves, Verônica de Medeiros; Nardi , Antônio Egídio; Figueiredo , Elaine Virginia Martins de Souza (Diversitas Journal, 2022)
the purpose of this study was to determine the correlation between impulsivity/aggressivity traits and mental disorders in cocaine/crack users. A non-probabilistic sample of the 106 subjects from an out-patient center for homeless people and three therapeutics communities in Northeast Brazil was investigated. The version of the Mini International Neuropsychiatric Interview 5.0 was used to assess lifetime psychiatric disorder. Impulsivity and aggressiveness were used in the Barratt Impulsivity Scale (BIS-11) and Buss–Perry Aggression Questionnaire (BPAQ), respectively. Individuals in cocaine/crack use report heightened levels impulsive and aggressive behavior. Linear regression results showed a positive correlation between total impulsivity and abuse of alcohol in our population. Considering impulsivity subscores, low levels of motor impulsivity, suicide risk, generalized anxiety disorder and antisocial personality disorder were negatively correlated. Past hypomanic episode was correlated positively with high non-planning impulsivity scores. These findings highlight the need for a continual investigation of mental disorder and its link with aggressive and impulsive personality traits in the cocaine/crack patients and these data can contribute to stratification for continuity treatment for these patients. Aggressiveness was correlated inversely with suicide risk, psychotic, mood and anxiety disorders. These findings highlight the need for a continual investigation of mental disorder and its link with aggressive and impulsive personality traits in the cocaine/crack patients and these data can contribute to stratification for continuity treatment for these patients.